Evaluation of the latex slide agglutination test for identification of Staphylococcus aureus. - Myrick, B A (1982)
This study evaluated the reliability of the latex slide agglutination test for identifying Staphylococcus aureus. A total of 806 clinical isolates of staphylococci were tested for latex agglutination, clumping factor, and free coagulase. Positive latex tests occurred in 98.3% of coagulase-positive strains, whereas 99.6% of coagulase-negative strains gave negative latex tests. It is concluded that in most instances, the latex slide agglutination test is a reliable method for identifying S. aureus in the clinical laboratory.